Reperfusion Therapy for ST-Elevation Myocardial Infarction at Dr. Soetomo General Academic Hospital Surabaya - Rosavelina Sintaasih Budihardjo; Agus Subagjo; Subur Prajitno (Cardiovascular and Cardiometabolic Journal, 2021)
Background: Cardiovascular disease is the number one cause of death in the world by killing 17,9 million people every year. The most frequent cardiovascular disease occurs as STEMI which related to the depiction of persistent depiction of EKG elevation with ST segment. This research is aiming for figure out the profile of reperfusion therapy at Dr. Soetomo General Academic Hospital, Surabaya. Methods: In this research, the data is collected using observation method, without any treatment applied with descriptive statistical analysis using table. The data collection techniques used is simple random sampling. Results: The STEMI patients at Dr. Soetomo General Academic Hospital Surabaya are dominated by referral patients (79,2%) from approximately 40 hospitals in East Java. Most of the patients were male, the ages between 51 – 60 years old with the most frequent risk factors was the combination of type 2 diabetes mellitus, hypertension, and smoking. The reperfusion therapy given was PCI with a door to balloon <120 minutes was 59.6%. Fibrinolytic that was done in <12 hours after onset was 82.9%. Patients with STEMI managed at Dr. Soetomo General Academic Hospital Surabaya, had mortality rates around 12.2%. Conclusion: Most of the STEMI patients in Dr. Sutomo General Academic Hospital Surabaya was a referral patient and had sufficiently good PCI and fibrinolytic reperfusion therapy, resulting in a low mortality rate.